Reduction in Syrinx Size and Severity After Venous Sinus Stenting in a Patient With Pseudotumor Cerebri and Chiari Malformation: Technical Case Report. Issue 2 (June 2016) - Chung, Charlotte Y.; John, Seby; Luciano, Mark G.; Hui, Ferdinand K.
Abstract : BACKGROUND AND IMPORTANCE: Pseudotumor cerebri and Chiari I malformation are found to coexist in a subset of patients. Surgical cranial decompression has been the mainstay of Chiari malformation management, whereas venous sinus stenting has emerged as an effective treatment modality for pseudotumor cerebri. Gaps in our current understanding of cerebrospinal fluid (CSF) circulation and the pathophysiology behind CSF-related disorders present difficulties in the simultaneous management of these conditions. A case is presented of the successful management of both conditions with venous sinus stenting, with sustained improvement in symptoms and structural abnormalities of the Chiari malformation and associated syrinxes. CLINICAL PRESENTATION: An obese woman in her 20s with a history of occipital headaches who presented with progressively worsening intermittent visual obscurations was diagnosed with pseudotumor cerebri, Chiari I malformation, and associated spinal syrinxes. Magnetic resonance venography demonstrated right transverse sinus narrowing with an elevated pressure gradient. Successful endovascular intervention with venous sinus stenting achieved normalization of the venous sinus pressure gradient and symptomatic improvement. After stenting, the cervical syrinx was observed to have decreased in size, with a decrease in the extent of cerebellar tonsillar herniation and an increase in CSF signal around the cerebellar tonsils. CONCLUSION: Venous sinus stenting for treatment of concomitant pseudotumor cerebri and Chiari I malformation can be effective in patients demonstrating transverse sinus stenosis. ABBREVIATIONS: CM, Chiari I malformation PTC, pseudotumor cerebri